(untitled) (Gestão & Regionalidade, 2018)
The purpose of this article is to analyze the social participation in the urban solid waste management from the perspective of social and environmental management. The National Solid Waste Policy has presented big challenges to municipalities, especially regarding social participation in integrated waste management. As a methodological procedure, a descriptive qualitative and quantitative study was conducted in Lavras (MG). The qualitative stage was conducted through semi-structured questionnaires applied to the public administration and to the Association of Recyclable Materials Collectors. The quantitative stage was conducted through structured questionnaires applied to a sample (significance level of 95% and sampling error of 5%) of the population from Lavras. The results show that the municipality is taking actions to meet up the policy, however there is a lack of social and environmental management in this process, especially regarding low social participation. Keywords: Social participation; National Solid Waste Policy; social management; environmental management.